2005
DOI: 10.1177/01650250500166824
|View full text |Cite
|
Sign up to set email alerts
|

Infants' social looking toward mothers and strangers

Abstract: This study investigated infant social looking in a social referencing procedure with mothers and strangers. Sixty-one infants and their mothers participated when the infants were 18 and 24 months old. The frequency and latency of looking toward each adult when the baby encountered remotecontrolled ambiguous toys were measured. Mothers and strangers (female experimenters) expressed positive or negative emotional responses whenever children looked toward them. Results indicated that older infants looked more oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
55
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 22 publications
6
55
2
1
Order By: Relevance
“…Referential looks are based in infants' looking behaviour towards adults when they need to understand situations, and are associated with infants' motivations to be actively involved in social communication (Stenberg, 2003;Walden & Kim, 2005). Most studies measured referential looks by calculating the number of infant's social looks at adults (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Referential looks are based in infants' looking behaviour towards adults when they need to understand situations, and are associated with infants' motivations to be actively involved in social communication (Stenberg, 2003;Walden & Kim, 2005). Most studies measured referential looks by calculating the number of infant's social looks at adults (e.g.…”
mentioning
confidence: 99%
“…Some researchers examined the latency of looks (how fast infants make an eye contact with adults; e.g. Walden & Kim, 2005) or the duration of looks (how long infants maintain the eye-contact with adults; e.g. Mumme et al, 1996).…”
mentioning
confidence: 99%
“…They found that stranger had lesser effect on the infant's behavior than their own mother. A more recent study and the only study, which used two simultaneous referees (mother and stranger) was Walden and Kim (2005). They tested infants aged 18 and 24 months for their social referencing behavior in terms of their frequency of looks given to each referee and found that the older infants preferred more frequently to the stranger than their mother.…”
mentioning
confidence: 99%
“…It is not too unreasonable to think that infants much younger than those in Walden and Kim (2005) are able to select referee, given the recent studies on young infants' ability to monitor and sensitivity towards their social partner's state, which seems to emerge during the latter half of the first year of life. For instance, Striano and Rochat (1999a) demonstrated evidence for a gradual emergence of referential looking behavior alternating between an object and a person.…”
mentioning
confidence: 99%
See 1 more Smart Citation